2022
DOI: 10.1371/journal.pntd.0010414
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study of community-acquired bacterial bloodstream infections in Metro Manila, the Philippines

Abstract: Community-acquired bacterial bloodstream infections are caused by diverse pathogens with changing antimicrobial-resistance patterns. In low-middle income countries in Southeast Asia, where dengue fever is endemic and a leading cause of fever, limited information is available about bacterial bloodstream infections due to challenges of implementing a blood culture service. This study describes bacterial bloodstream pathogens and antimicrobial-resistance patterns in Metro Manila, the Philippines. We aimed to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…The AUCs for Dataset 1 (0.83, 95% CI: (0.81, 0.84)) and Dataset 4, Day-3 (0.82, 95% CI: 0.77, 0.88)) were close to the AUCs reported by (8) and (23) (0.83 and 0.84, respectively), while the AUC for Dataset 4, Day-1 (0.86, 95% CI: (0.81, 0.90)) was slightly lower than the value of 0.93 reported by Park et al (23). AUC values were not reported by Gasem et al (25) and Saito et al (21) for Datasets 2 and 3; we found respective AUC values of 0.89 (95% CI: (0.87, 0.91)) and 0.85 (95% CI: (0.83, 0.87)), demonstrating relatively good predictive performance.…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…The AUCs for Dataset 1 (0.83, 95% CI: (0.81, 0.84)) and Dataset 4, Day-3 (0.82, 95% CI: 0.77, 0.88)) were close to the AUCs reported by (8) and (23) (0.83 and 0.84, respectively), while the AUC for Dataset 4, Day-1 (0.86, 95% CI: (0.81, 0.90)) was slightly lower than the value of 0.93 reported by Park et al (23). AUC values were not reported by Gasem et al (25) and Saito et al (21) for Datasets 2 and 3; we found respective AUC values of 0.89 (95% CI: (0.87, 0.91)) and 0.85 (95% CI: (0.83, 0.87)), demonstrating relatively good predictive performance.…”
Section: Resultscontrasting
confidence: 75%
“…Saito et al (21) collected data on 1573 patients aged 1–85, with a fever lasting at most 21 days and suspected of bloodstream infection, in the Philippines from 2015 to 2019. Of these patients, 256 (16.3%) were diagnosed with dengue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation